2005
DOI: 10.1176/appi.ap.29.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students' Attitudes Toward Mental Disorders Before and After a Psychiatric Rotation

Abstract: Participation in a psychiatry rotation can strengthen student attitudes about biologically- and socially-based causes and community based treatments for mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Portuguese medical students have similar results to some studies that showed good or better attitudes towards the psychiatric patients in late medicine school years, 23 after psychoeducation [24][25][26][27][28][29] and psychiatric teaching. [30][31][32] Although our students' attitudes showed a regression in scores after the third year, they were still better at the end of the course than the in first year. Anyway we shall be aware of the bias of age, as older students may have better attitudes when compared to younger students.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Portuguese medical students have similar results to some studies that showed good or better attitudes towards the psychiatric patients in late medicine school years, 23 after psychoeducation [24][25][26][27][28][29] and psychiatric teaching. [30][31][32] Although our students' attitudes showed a regression in scores after the third year, they were still better at the end of the course than the in first year. Anyway we shall be aware of the bias of age, as older students may have better attitudes when compared to younger students.…”
Section: Discussionmentioning
confidence: 54%
“…10,13,20 Nevertheless this positive impact wasn't long lasting and this could be due, as stated, to contamination of negative attitudes towards the psychiatric disorders from teachers to students and negative attitudes held towards psychiatry and psychiatrists by their medical educators, among other factors that are mostly present in late medicine school years. 28,30,31 …”
Section: Discussionmentioning
confidence: 99%
“…6 There are conflicting reports as to whether workplace experience reduces social distance from people with mental illness. [7][8][9] Contacts between pharmacy students and people with mental illness during clinical placements typically occur in the context of a provider-patient interaction. This kind of interaction may not contribute to students developing a greater understanding of a consumer's experience of their illness.…”
Section: Use Of Consumer Educators In Mental Health Pharmacy Educationmentioning
confidence: 99%
“…The principal investigator constructed the interview questions (see Table 1) from previous medical student self-report questionnaire findings (Cutler et al 2006), as well as from a general review of existing psychiatric education literature (Feifel et al 1999;Chew-Graham et al 2003;Fink 1983;Walter 1989;Furnham 1986;Cutler et al 2006;Galka et al 2005;Martin et al 2005;Singh et al 1998;Balon et al 1999;Sierles and Taylor 1995;Nielsen and Eaton 1981). Two faculty members in the department of psychiatry conducted the interviews shortly after students received notification of their residency matches.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…While enrolled medical students in the United States find the field intellectually interesting (Cutler et al 2006), many regard clinical work with psychiatric patients as unappealing (Galka et al 2005;Martin et al 2005;Singh et al 1998;Balon et al 1999;Sierles et al 1995;Nielsen et al 1981) and even stressful (Cutler et al 2006). Similar observations have been made in many countries around the world (Brockington and Mumford 2002;Malhi et al 2002;Fischel et al 2008;Ndetei et al 2008;Syed et al 2008;Ay et al 2006).…”
Section: Introductionmentioning
confidence: 99%